Crystal structure of 1-{4-hydroxy-3-[(pyrrolidin-1-yl)methyl]phenyl}-3-phenylprop-2-en-1-one - Yerdelen, Kadir Özden; Gül, Halise İnci; Aydin, Abdullah; Celik, Raziye Catak; Akkurt, Mehmet (International Union of Crystallography (IUCr), 2016)
In the title compound, C20H21NO2, the pyrrolidine ring adopts an envelope conformation with the N atom at the flap position. The central benzene ring makes dihedral angles of 21.39 (10) and 80.10 (15)° with the phenyl ring and the mean plane of the pyrrolidine ring, respectively. The molecular conformation is stabilized by an intramolecular O—H...N hydrogen bond, which closes anS(6) ring. A weak C—H...π interaction is observed in the crystal.
Keywords: crystal structure; Crystallography; intramolecular O—H...N hydrogen bond; methylphenyl; Research Communications; Mannich Bases; intramolecular O-H center dot center dot center dot N hydrogen bond; QD901-999; Mannich bases; Semi-Empirical; Crystal Structure; Methylphenyl; semi-empirical; 3. Good health